The longitudinal profile of CSF markers during external lumbar drainage. Issue 10 (16th June 2009) - Tarnaris, A; Toma, A K; Chapman, M D; Petzold, A; Kitchen, N D; Keir, G; Watkins, L D
Abstract : Background: External lumbar drainage (ELD) is known as a good predictor of favourable outcome in shunting patients suffering from idiopathic normal pressure hydrocephalus (iNPH). Methods: Eleven patients suffering from iNPH had a lumbar drain (LD) inserted for 72 h and participated in a research study to quantify any improvement in their clinical symptoms. The lumbar cerebrospinal fluid (CSF) levels of lactate, 8-isoprostane, vascular endothelial growth factor (VEGF), glial fibrillar acidic protein (GFAP), neurofilament (heavy chain) protein (NF (h)), Aβ1–42 (β-amyloid) and total tau were assayed samples from all three time points. Results: The concentrations of lactate, VEGF, GFAP and tau increased significantly during the 72 h of drainage. There were also increases in 8-isoprostane and Aβ1–42 (non significant). The concentration of NF (h) was reduced significantly following 72 h of drainage. There was a significant positive correlation between Aβ1–42 and total tau in the first sample. GFAP was negatively correlated in a significant fashion with both Aβ1–42 and total tau. NF (h) was negatively correlated with VEGF. Conclusion: Evidence is provided that ELD is producing measurable changes in the CSF composition of patients with iNPH. The present paper discusses how such changes may be implicated in the pathophysiology of the condition.